2023
DOI: 10.3390/fermentation9090824
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Saccharomyces Yeasts from Cider Produced in Hardanger

Urban Česnik,
Mitja Martelanc,
Ingunn Øvsthus
et al.

Abstract: Saccharomyces cerevisiae is commonly used for the production of alcoholic beverages, including cider. In this study, we examined indigenous S. cerevisiae and S. uvarum strains, both species commonly found in cider from Hardanger (Norway), for their strain-specific abilities to produce volatile and non-volatile compounds. Small-scale fermentation of apple juice with 20 Saccharomyces strains was performed to evaluate their aroma-producing potential as a function of amino acids (AAs) and other physicochemical par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Yeasts produce 4-vinyl phenol (4VP) and 4-vinyl guaiacol (4VG) via the decarboxylation of hydroxycinnamic acids. Since apple juice is rich in precursor cinnamic acids, in cider the concentrations of 4VP and 4VG can reach high levels, considerably impacting the organoleptic quality [36]. Indeed, data demonstrated rather high concentrations of 4VP and 4VG for S. cerevisiae, exceeding the odor threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Yeasts produce 4-vinyl phenol (4VP) and 4-vinyl guaiacol (4VG) via the decarboxylation of hydroxycinnamic acids. Since apple juice is rich in precursor cinnamic acids, in cider the concentrations of 4VP and 4VG can reach high levels, considerably impacting the organoleptic quality [36]. Indeed, data demonstrated rather high concentrations of 4VP and 4VG for S. cerevisiae, exceeding the odor threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Selected volatile organic compounds (VOCs) were determined in the wine samples using an automated robotic system for solid-phase micro-extraction (SPME) in headspace (HS) and injected into a gas chromatograph coupled with a mass spectrometric detector (GC-MS). Esters, C6 alcohols, and volatile phenols were analyzed using two methods adapted from a previously published protocol [8,9]. Samples were extracted by headspace Solid Phase Micro-Extraction (HS-SPME) using an SPME fiber assembly (50/30 µm DVB/CAR/PDMS, Stableflex, 24 Ga, Autosampler, Gray (Supelco, St. Louis, MO, USA).…”
Section: Determination Of Volatile Compoundsmentioning
confidence: 99%
“…The yeast species and strains used for fermentation have a huge impact on the volatile compound profile of wines and ciders [ 88 , 91 , 106 , 107 ]. The strains of the species Saccharomyces cerevisiae (Johannisberg Riesling and Steinberg) have been demonstrated to influence the profile of volatile compounds in apple wines.…”
Section: Volatile Compounds Of Apple Wines and Cidersmentioning
confidence: 99%
“…There is a considerable degree of diversity within a given species of yeast in its ability to synthesise compounds that influence cider aroma, and this depends on the strain used. Cesnik et al [ 106 ] employed 14 strains of Saccharomyces uvarum and 6 strains of Saccharomyces cerevisiae for cider fermentation. The authors showed that, in certain instances, there were notable discrepancies in the production of volatile compounds between the two species, and, in other cases, between particular strains, even within the same species.…”
Section: Volatile Compounds Of Apple Wines and Cidersmentioning
confidence: 99%
See 1 more Smart Citation